PERAN KEJAKSAAN NEGERI HUMBANG HASUNDUTAN DALAM PENANGANAN TINDAK PIDANA KORUPSI DI WILAYAH KABUPATEN HUMBANG HASUNDUTAN (STUDI PUTUSAN NOMOR 91/PID-SUS TPK/2024/PN.MDN) - Angeline Siahaan, Yohanna; Mulyadi, Mahmud; Cita Emia Tarigan, Vita (Penerbit Lafadz Jaya, 2025)
Article 1 point 1 of Law Number 16 of 2004 concerning the Attorney General's Office of the Republic of Indonesia stipulates that the Attorney is a functional official authorized by this law to act as a public prosecutor and implementer of court decisions that have obtained legal force and other authorities based on the law. The Attorney General's Office of the Republic of Indonesia as a state government institution that exercises state power in the field of prosecution must be free from the influence of any party's power, namely carried out independently regardless of the influence of government power and the influence of other powers. The Attorney General's Office as one of the law enforcement institutions is required to play a greater role in upholding the supremacy of law, protecting public interests, upholding human rights and eradicating corruption, collusion and nepotism (KKN).